Associations between abdominal fat, psoas muscle fat, and lumbar spine bone density: insights from quantitative CT imaging - Xu, Hua; Wang, Zhi; Meng, Xiang-hong; Zhu, Feng-ling; Zhong, Yu-qiao (BMC musculoskeletal disorders, 2025)
Purpose To investigate the correlation between abdominal adipose tissue (AAT), psoas muscle fat content, and lumbar vertebral bone mineral density (BMD) in different age and sex groups using quantitative CT(QCT) imaging. Methods A total of 861 subjects were included in this study, comprising 404 males and 457 females, divided into 6 age groups. According to the BMI classification criteria, individuals are divided into four groups. QCT was used to measure BMD, visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), and psoas muscle fat content (Fp). Independent sample t-tests were used to compare intergroup differences in the above data between males and females in the same age group. One-way analysis of variance (ANOVA) was used to compare intergroup differences in the data between males and females in each age group. Kruskal-Wallis H test was used to compare QCT measurements among different BMI groups. Pearson correlation analysis was used to assess the correlations of BMD with BMI, VAT, SAT, and Fp, as well as the correlation between AAT and Fp. Results There was no difference in Fp between males and females in each age group. In the 60–69 and 70–79 age groups, female BMD was significantly lower than that of males ( P < 0.001). Except for the 20–29 and 40–49 age groups, the SAT in females was higher than that of males ( P < 0.001), while except for the 20–29 age group, female VAT was lower than that of males ( P < 0.001) in each age group. There were differences in BMD (F = 72.07, P < 0.001), VAT (F = 22.12, P < 0.001), and Fp (F = 23.61, P < 0.001) among different age groups in males. Among different age groups in females, there were differences in BMD (F = 188.81, P < 0.001), VAT (F = 39.82, P < 0.001), SAT (F = 6.26, P < 0.001), and Fp (F = 26.22, P < 0.001). Among different BMI groups there were differences in BMD, VAT, SAT and Fp ( P < 0.001). BMD in males was negatively correlated with both VAT and Fp ( R =-0.336, -0.422, P < 0.001), and Fp was positively correlated with VAT and SAT ( R = 0.405, 0.125, P < 0.001). BMD in females was negatively correlated with BMI, SAT, VAT, and Fp ( R =-0.170, -0.112, -0.509, -0.469, P < 0.001), and Fp was positively correlated with VAT and SAT ( R = 0.521, 0.325, P < 0.001). Conclusion VAT and psoas muscle fat content increase with age, while BMD decreases with age. Increased VAT, psoas muscle fat content, and SAT in females may be risk factors for osteoporosis. Clinical trial number Not applicable.